FACTORS DETERMINING THE GROWTH OF COSTS IN THE INSURANCE SYSTEM AGAINST INDUSTRIAL ACCIDENTS IN UKRAINE - BLAZHYNSKA, Tetiana (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article analyzes the factors determining costs in the system of insurance against accidents at work and their economic and social consequences. The increase in costs in this system increases the burden on employers who pay insurance contributions, as well as the burden on the social insurance system of Ukraine, which negatively affects public finances and the country’s economy in general. This can lead to an increase in the prices of goods and services, as well as a decrease in the country’s attractiveness for investment. Occupational accidents are an unfavorable social phenomenon that primarily negatively affects the life and health of an employee, and at the same time an insured event, the occurrence of which necessitates the payment of insurance compensation to the victim. For this reason, the disability insurance system is an important tool of the social protection system, which protects employees from material losses in the event of a disability. The disability insurance system has been operating in Ukraine since 1998. Over this time, it has undergone significant changes, including an increase in the list of insured events, higher tariffs, and larger benefit amounts. However, despite these changes, the costs of the disability insurance system continue to grow. According to the Social Insurance Fund of Ukraine, the cost of disaster insurance payments in 2022 increased by 15%, reaching UAH 12.2 billion.